Could minors be living kidney donors? A systematic review of guidelines, position papers and reports. (8th April 2013) - Thys, Kristof; Van, Kristof; Nobile, Hélène; Siebelink, Marion; Aujoulat, Isabelle; Schotsmans, Paul; Dobbels, Fabienne; Borry, Pascal
Summary The purpose of this study is to systematically review guidelines, position papers, and reports on living kidney donation by minors. We systematically searched the databases such as Medline, Embase, ISI Web of knowledge, Google scholar as well as the websites of various bioethics committees, transplant organizations and societies. Guidelines were included if they provided recommendations for or against living kidney donation by minors. Data were analyzed using qualitative content analysis. We included 39 documents in this study. Twenty seven of these endorse an absolute prohibition of living kidney donation by minors, because of concerns regarding the decision‐making capacity of minors, the impartiality of parental authorization, the best interests of the minor, and the necessity of the donation. Twelve guidelines, however, would exceptionally allow living kidney donation by minors, provided that adequate safeguards are put in place, including an assessment of the minor's autonomy and maturity, authorization by an independent body, assuring that the anticipated psychosocial benefits outweigh the medical and psychosocial risks for the donor and the restriction to situations of last resort. A more adequate medical and psychosocial follow‐up of living kidney donors may likely contribute to a more unified approach towards living kidney donation by minors.